Do inside directors affect sustainability performance? A test of a contingency approach - Galbreath, Jeremy (ANZAM, 2013)
As boards are increasingly responsible for addressing sustainability and accountable for the extent to which they do so, this study's point of departure is to examine the impact of inside directors on sustainability performance. By creating an aggregate measure that accounts for economic, environmental, and social metrics, this study finds that insiders are negatively related to sustainability performance. However, when the variables of compensation linked to environmental and social metrics, sustainability training, and comprehensive company codes of conduct are introduced, their interactive effects positively moderate the insider-sustainability performance relationship. Implications of findings are discussed, along with future research directions and limitations.